Pengaruh Citra Merek dan Kualitas Produk Serta Desain Produk Terhadap Keputusan Pembelian Smartphone Oppo di Badilan Grosir Singaraja - Yanti, Ni Kadek Deni Karmini; Telagawathi, Ni Luh Wayan Sayang (Jurnal Pendidikan Ekonomi Undiksha, 2021)
This research aims to examine the effect of brand image and product quality as well as product design on purchasing decision, either simultaneously or partially. The research design used in this research is causal quantitative. The subjects in this research are consumers who own an Oppo Smartphone and buy it at Badilan Grosir Singaraja and the objects of this research are brand image, product quality, product design and purchase decisions. The sample in this study amounted to 100 respondents. The data were collected by means of a questionnaire and analyzed using multiple linear regression analysis. The results showed that (1) brand image and product quality and product design had a positive and significant effect on purchasing decisions (2) brand image had a positive and significant effect on purchasing decisions (3) and product quality had a positive and significant effect on purchasing decisions (4) Product design has a positive and significant effect on the purchase decision of an Oppo Smartphone at Badilan Grosir Singaraja.